Lost in transition: What refugee post‐migration experiences tell us about processes of social identity change. (5th May 2021) - Ballentyne, Susie; Drury, John; Barrett, Emma; Marsden, Sarah
Abstract: This paper presents findings based on over 40 hrs of rich, phenomenological narrative interview data in which five Syrian refugees describe their experiences of transitioning to a new life in Brazil. Using the Social Identity Model of Identity Change (SIMIC) as a framework for examining the relationship between a period of vulnerability, multiple social identities and wellbeing, interviews were combined with a "talking stones" technique. Key themes of identity "recovery" and "discovery" were consistent with the identity "gain" and "continuity" components of SIMIC. A theme of "adaptation" suggested that a process of continual identity construction and reconstruction is central to both outcomes. Further, themes relating to identity "constraint" suggests how some contexts can actively freeze identities, thus undermining agency and compromising wellbeing. The refugee stories analysed in this paper demonstrate how the SIMIC is a robust model for capturing many of the identity complexities within post‐migration life. Please refer to the supplementary material section to find this article's Community and Social Impact Statement .